(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The relevance of this study is due to the fact that some schools of folk art lose their uniqueness and originality over the years, which contributes to the loss of cultural and national traditions in the work of many peoples. In this regard, it seems relevant to study the originality and pedagogical significance of the Ferghana Kokand ornament, which is distinguished by originality, history and integrator of elements from other schools of folk art. The purpose of this article is to identify the features, the pedagogical heritage of the endangered type of the Kokand ornament, as well as to study the creativity of the masters, which will contribute to the further development of applied art in the Republic of Uzbekistan. During the study, the following methods were used: historicity, periodicity, comparative, practical work, logical analysis, which allowed.